A case study of informed consent in Indonesian Law Number 29, 2004 - Agung Sosiawan; Vera Rimbawani Sushanty; Dian Agustin Wahjuningrum; Fery Setiawan (Universitas Airlangga, 2023)
Background: Informed consent is an agreement between the doctor/the provider of medical services and the patient/the recipient of medical services. This relationship between these parties has changed from a paternalistic to a contractual relationship due to technological shifts. Doctors are obliged to notify the patient of all the risks and benefits of a procedure while respecting their autonomy by not intervening the decision-making process. This article will look at three government and academic hospitals in Surabaya, as informed consent has to be practiced in all medical settings. Purpose: This study aims to review the role of informed consent according to Law Number 29, 2004. Review: This study aims to discuss the characteristics of informed consent under Law Number 29, 2004, because there are too few articles addressing this issue. It also explains the roles of the patient and the doctor/dentist in informed consent according to this piece of legislation. Conclusion: According to Article 184, informed consent provides vital evidence that can be used to hold doctors and dentists legally accountable because it contains information about standard operating procedures (SOPs) that medical professionals are legally required to follow. Guidelines for informed consent are given in Law Number 29, 2004, Article 45, paragraph 2.